Implementasi Peraturan Pemerintah (Nomor 23 Tahun 2018) Pada Usaha Mikro Kecil Dan Menengah - Geby Liany; Mohamad Ilham (Musamus Accounting Journal, 2019)
This research aims to find out how micro small and medium enterprises in Merauke District have known and obeyed the provisions of government Regulation number 23 year 2018. The object of this research is SMES in Merauke Regency with the number of samples of 9 SMES listed as taxpayers and employees of KPP Merauke. This research uses qualitative methods. The results of the research of most SMES are aware of and comply with the provisions of government Regulation Number 23 year 2018 although still found taxpayers are still late when making tax payments and some are not yet obedient due to lack of Information and understanding as taxpayers. In the case of taxpayers ' compliance, known SMES actors belong to formal compliance that is carrying out the tax administration obligations but not yet legally compliant. Keywords: UMKM, Compliance